The relationship between body mass index, waist circumference and psoriatic arthritis in the Turkish population - Ozkaya, Dilek Biyik; Onsun, Nahide; Topukçu, Bugce; Su, Ozlem; Bahalı, Anil Gulsel; Dizman, Didem; Rezvani, Aylin; Uysal, Omer (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction : Psoriasis is a chronic, immune-mediated inflammatory disease predominantly affecting the skin, with a complex aetiology. Recently it has been suggested that the chronic inflammation of psoriasis may cause metabolic and vascular disorders. The relationship between obesity and psoriatic arthritis (PsA) is not clear, and there are insufficient prospective studies addressing this subject. Aim : To investigate the relationship between psoriatic arthritis, severity of psoriasis and obesity in the Turkish population. Material and methods : Patient data from psoriasis outpatient clinics from February 2007 to July 2013 were reviewed retrospectively using the Psoriasis-Turkey (PSR-TR) registration system. Patients’ age, onset age, body mass index (BMI), waist circumference, psoriasis area and severity index (PASI), and arthritis information were reviewed. In the outpatient clinics, patients who had joint pain consulted rheumatology clinics. The CASPAR criteria were used for the diagnosis of arthritis. Results : A total of 443 males and 495 females enrolled in this study. The mean age of females was 43.9 years (18–93 years) and the mean age of males was 44.6 years (18–89 years). A total of 231 (25%) patients had psoriatic arthritis. Investigation of the relationship between PASI, BMI, waist circumference (WC) and arthritis revealed a statistically significant relationship between each variable. Conclusions : In this study we observed a relationship between PsA and high BMI, high WC and high PASI. Psoriatic arthritis is a chronic inflammatory disorder and a chronic inflammatory state induced by adiposity may lead to PsA.